(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article describes the role of environmental control and its importance in the use and protection of agricultural land. Based on scientific and legal controversy, the role of environmental control and its significance is substantiated. The legislation of national and foreign countries related to environmental control in the use and protection of agricultural land has been scientifically and theoretically analyzed. The system of environmental control in the field of rational use of agricultural land and their protection is explained. Currently, the activities carried out in the field of organization and protection of agricultural land use were analyzed.